The p53-inducible gene 3 involved in flavonoid-induced cytotoxicity through the reactive oxygen species-mediated mitochondrial apoptotic pathway in human hepatoma cells. Issue 5 (13th May 2015) - Zhang, Qiang; Cheng, Guangdong; Qiu, Hongbin; Zhu, Liling; Ren, Zhongjuan; Zhao, Wei; Zhang, Tao; Liu, Lei
<x xml:space="preserve">Abstract</x> PIG3 is a key regulator that is responsible for the prooxidant activity and apoptosis-inducing effect of flavonoids on cancer cells.